Engineered Smart Textiles and Janus Microparticles for Diverse Functional Industrial Applications. Issue 3 (11th February 2019) - Saini, Shubham; Kandasubramanian, Balasubramanian
ABSTRACT: Janus materials are biomimetically inspired systems with two or more functional properties arising as paramount materials for utilization in different fields like Medical, Protective clothing etc. Janus particles can be in different forms like capsule, fiber, nano cage, disc, nano film etc. which are amalgamated with fabric by different processes. Based on the fabrication and constituent elements, Janus materials can be fabricated by incorporating multiple properties like fire-retardancy, catalytic property, thermal regulation etc. This review article enumerates the numerous industrial applications of the Janus fabrics and simultaneously outlines the extensive methodologies utilized for engineering of the Janus fabrics. GRAPHICAL ABSTRACT: